2011
DOI: 10.1007/s00436-011-2609-8
|View full text |Cite
|
Sign up to set email alerts
|

Parasitic infections and myositis

Abstract: Infectious myositis may be caused by a wide variety of bacterial, fungal, viral, and parasitic agents. Parasitic myositis is most commonly a result of trichinosis, cystericercosis, or toxoplasmosis, but other parasites may be involved. A parasitic cause of myositis is suggested by history of residence or travel to endemic area and presence of eosinophilia. The diagnosis of parasitic myositis is suggested by the clinical picture and radiologic imaging, and the etiologic agent is confirmed by parasitologic, sero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 225 publications
(252 reference statements)
0
12
0
3
Order By: Relevance
“…Bei Toxoplasmose, einer verwandten Parasitose, wirkt Pyrimethamin plus Sulfadiazin am effektivsten gegen Tachyzoiten, jedoch nicht gegen die späteren, enzystierten Bradyzoiten [5,28,31]. Für die seltene Toxoplasmose-Polymyositis wurde in der Akutphase ein Effekt der Antiprotozontherapie beschrieben, während die chronische Phase eine Steroidgabe erforderte [4,7]. Cotrimoxazol erscheint daher im frühen Stadium therapeutisch erfolgversprechend.…”
Section: Zusammenfassung ▼unclassified
“…Bei Toxoplasmose, einer verwandten Parasitose, wirkt Pyrimethamin plus Sulfadiazin am effektivsten gegen Tachyzoiten, jedoch nicht gegen die späteren, enzystierten Bradyzoiten [5,28,31]. Für die seltene Toxoplasmose-Polymyositis wurde in der Akutphase ein Effekt der Antiprotozontherapie beschrieben, während die chronische Phase eine Steroidgabe erforderte [4,7]. Cotrimoxazol erscheint daher im frühen Stadium therapeutisch erfolgversprechend.…”
Section: Zusammenfassung ▼unclassified
“…Treatment of underlying bacterial or fungal infections can often lead to acute recovery (1). However, for many viruses and parasites, poor druggability and effective immune evasion results in chronic infection and long-term myopathy (1, 57). Furthermore, while some pathogens can directly cause skeletal muscle damage, previous studies, in other sites of infection, have shown that infection can lead to immunologic scarring and reprogramming that potentiates aberrant immune-mediated pathology (8).…”
Section: Introductionmentioning
confidence: 99%
“…Myositis with eosinophilic infiltrates most commonly involves parasites [ 17 , 21 ] ( Trichinella , Echinococcus , Taenia solium , and Toxoplasma gondii ), viruses (EBV and coxsackie), inflammatory myopathies (dermatomyositis, polymyositis), and systemic diseases (Churg-Strauss syndrome) [ 13 ]. Other less common etiologies like muscular dystrophies (calpainopathy [ 8 ] and Becker Disease [ 14 ]), toxic exposures to L-tryptophan [ 7 ], toxic oil syndrome, malignancy, and EM as a component of idiopathic hypereosinophilic syndrome (HES) can also have eosinophilic predominant myositis [ 13 ].…”
Section: Discussionmentioning
confidence: 99%